Incorporating Advising Strategies into One-to-One Tutoring: Effects on the Awareness Towards Vocabulary Learning - Aydın, Doğuş; TÜTÜNİŞ, BİRSEN (Kanda University of International Studies, 2021)
Language advising helps a language learner discover different ways of learning and enables him/her to make decisions for better learning. This paper reports on an inquiry conducted with one English language learner who had difficulty with vocabulary acquisition which led to a perceived lack of progress in learning. The main purpose of the research was to observe and interpret the experience of the learner in terms of how different teaching and learning strategies appeared to affect her vocabulary learning. Qualitative research instruments including a semi-structured interview and a diary were used for this study. The results showed an increase in the learner's control over her vocabulary learning process which was likely facilitated by the incorporation of language advising strategies into individual private tutoring.
Keywords: Language Advising; Vocabulary Learning Strategies; Learner Autonomy; Individual Private Tutoring